(untitled) (Research, Society and Development, 2021)
The aim of this study was to identify the morphological and pedogenetic features of the soils and their chemical and physical characteristics in the hydrographic basin of the Middle Course of Rio Teles Pires (BHMTP). For this, six soil profiles were studied, in trenches, along the right and left banks of the Teles Pires River, located at the Encanto da Natureza Farm, São José Farm, Teles Pires River, Estrada do Espanhol Farm, Bonfim Community and Vaca Farm White. Descriptive morphological analyzes were carried out on each horizon and subsequently soil was collected for physical and chemical analysis. Through the interpretation of the morphological evaluations of the profiles, associated with the results of physical-chemical analyzes of the soils, it is possible to classified up to the fourth categorical level, two ARGISSOLO VERMELHO-AMARELO Distrófico típico (PVAd), located on the left bank of the river, two Oxisols, LATOSSOLO VERMELHO Eutrófico típico (LVe) e LATOSSOLO VERMELHO-AMARELO Distrófico típico (LVAd) located on the right side of the river, a GLEISSOLO HÁPLICO Tb Distrófico plintossólico (GXbd) located on the left and a CAMBISSOLO HÁPLICO Tb Distrófico (CXbd) Teles Pires River.. In general the soils showed medium textures in all profiles. Saturation by Al3+, it was high in most horizons, reflecting low pH values and lower levels of Ca2+, Mg2+, K+ and, consequently, lower base saturation, except LVe. Except for LVe, whose CTC was high, all soils showed average cation exchange capacity (CTC), a fact that reflects the typical mineralogy of weathered soils.